Proximate composition, starch properties and functionality in selected aquatic macrophytes - Syed, Nurul Nur Farahin (2019)
A total of six freshwater macrophytes, Colocasia esculenta, Eleocharis dulcis, Nelumbo nucifera, Sagittaria sagittifolia, Trapa bispinosa, Typha angustifolia, and one marine macrophyte, Enhalus acoroides were collected and divided into their vegetative (leaf and petiole), reproductive (pollen) and storage (seed, corm, rhizome and root) organs. All of these parts were determined for their proximate composition including moisture, ash, crude lipid, crude fiber, crude protein, Nitrogen Free Extract (NFE) contents. Proximate analysis showed that leaf part of freshwater macrophytes had higher moisture (T. angustifolia, 16.24%) and lipid (C. esculenta, 4.29%), whereas N. nucifera petiole had higher fiber content (42.60%) compared to others. Also, storage organs of different species had higher ash (S. sagittifolia root, 25.65%), protein (N. nucifera rhizome, 20.44%) and NFE (T. bispinosa seed, 72.32%) content. Marine macrophytes, E. acoroides were observed with higher moisture and ash in root part (18.92% and 27.06% respectively), whereas leaf part displayed higher lipid (2.49%), fiber (21.66%) and protein (13.58%) contents. The seed of E. acoroides had higher NFE (59.93%) compared to its leaf (24.73%). Plant parts with high NFE content (>50%); T. bispinosa seed (72.32%), C. esculenta corm (68.39%), T. angustifolia pollen (65.62%), N. nucifera seed (63.97%), E. dulcis corm (63.31%), N. nucifera rhizome (60.21%), E. acoroides seed (59.93%), S. sagittifolia corm (56.16%), E. acoroides rhizome (55.41%) and T. angustifolia rhizome (51.27%), were selected and further analyzed in detailed for their starch properties (size, shape and hilum) and functionality (starch gelatinization, crystallinity and rheological behavior) by extracting their native starches. Starch granules of aquatic macrophytes were as simple granules except for C. esculenta corm and N.nucifera. Size of starch granules from freshwater macrophytes ranged from smaller granules of T. angustifolia pollen (0.40-4.00 μm) to larger granules of N. nucifera rhizome (5.00-40.00 μm) whereas, for marine macrophytes, E. acoroides rhizome starch granules were with bigger size (28.85-53.84 μm) compared to its seed (4.59-28.00 μm). Based on the shapes, polygonal, irregular and oval were observed in C. esculenta corm and T. angustifolia pollen; elongated and longitudinal granules in T. bispinosa seed and E. acoroides rhizome; oval, round and ellipsoidal for the rest of the species. The round and oval shapes of starch granules were mostly observed with centric hilum whereas elongated granules had eccentric hilum. Eleocharis dulcis corm starch had significantly higher total starch content (90.87%) followed by corms of C. esculenta (82.35%) and S. sagittifolia (71.71%), in which are comparable with commercial starches. Amylose to amylopectin ratio shows that only N. nucifera seed categorized as high amylose starch (71.45:28.55%) while N. nucifera rhizome, T. bispinosa seed, C. esculenta corm and T. angustifolia rhizome as waxy starch with low amylose content, 7.63%, 8.83%, 10.61% and 13.51% respectively. On the other hand, parts with higher total starch and amylose contents were analyzed in E. acoroides rhizome (67.97% and 25.39% respectively). Non-starch components like protein was high in most starches (3.06-26.47%) as well as lipid contents (0.24-5.57%) affected the starch purities, whereas phosphorus contents (0.02-0.43%) association with starch increased the starch functionality. Glucose was present in all of the samples range between 0.19 g 100 g-1 - 0.25 g 100 g-1. Total sugar contents were comparatively low ranging from 0.40 g (T. angustifolia rhizome) to 1.71 g (C. esculenta corm) whereas comparable values were observed in E. acoroides seed (0.63 g) and rhizome (0.57 g). The functional properties of native starches are important analysis in order to define its values, whether they are attainable or need some modification to achieve the desired results. Based on thermal properties, higher gelatinization temperature on both onset and peak were observed in marine macrophytes of E. acoroides rhizome (62.35°C and 96.46°C respectively) whereas lower temperatures were detected in freshwater macrophytes, T. angustifolia pollen (41.63°C and 74.62°C respectively). High-amylose of N. nucifera seed and T. angustifolia pollen resulted in higher gelatinization enthalpy (19.93 and 18.66 Jg-1 respectively) while lower enthalpy was in both E. acoroides seed (7.72 Jg-1) and rhizome (4.30 Jg-1). In the present study the lotus seed had higher digestible starch (44.36%) compared to its RS (27.94%). Higher RS was observed mostly in rhizome part (E. acoroides>N. nucifera>T. angustifolia) compared to others. Functional properties showed the XRD profiles of aquatic macrophytes starches displayed that all the corms starches, N. nucifera seed, and marine macrophytes, E. acoroides seed had A-type crystallinity. The T. bispinosa seed had CA-type whereas rhizomes part (N. nucifera and E. acoroides) and T. angustifolia pollen starch exhibited CB-type crystallinity. Waxy starches of C. esculenta corm had higher relative crystallinity (36.91%) and viscosity (46.2 mPas) with compared to regular starches. In conclusion, these selected aquatic macrophytes show its storage organs has good potential in starch-based food production based on their carbohydrate content and starch properties. Details on their starch granules properties and functionality are very important in order to obtain its suitability in food formulation and non-food application industries.